New Frontiers in Interregional Migration Research (Advances in Spatial Science, The Regional Science Series,, 2018)
This book focuses on the latest advances and challenges in interregional migration research. Given the increase in the availability of "big data" at a finer spatial scale, the book discusses the resulting new challenges for researchers in interregional migration, especially for regional scientists, and the theoretical and empirical advances that have been made possible. In presenting these findings, it also sheds light on the different migration drivers and patterns in the developed and developing world by comparing different regions around the globe. The book updates and revisits the main academic debates in interregional migration, and presents new emerging lines of investigation and a forward-looking research agenda.